Complicaciones postoperatorias en el trasplante hepático. Relación con la mortalidad. - Seller Pérez, Gemma Luisa; Herrera-Gutiérrez, Manuel Enrique; Aragonés Manzanares, Rocío; Muñoz López, Alfonso; Lebrón-Gallardo, Miguel; González Correa, José Antonio (Elsevier, 2004)
Background and objective: Liver transplant is an effective procedure for fulminant hepatitis or chronic liver disease and offers an adequate quality of life. However, even though it is a consolidated treatment, patients can develop serious complications in the immediate postoperative course. Patients and method: Prospective observational study of 131 patients admitted in our intensive care unit after liver transplant surgery. We studied variables related with the development of complications and their relation to outcome. Results: Intensive care unit mortality was 11.5%. Median stay was 4 days. 90% of patients presented 2 or more complications. Hyperglycemia, thrombocytopenia and hypothermia were the most frequent complications but they were not related with mortality. Less frequent but related to outcome complications were acute renal failure (23.6% mortality vs. 1.3%; p < 0.01), ADRS (63.6% vs 6.7%; p < 0,01), low cardiac output (71.4% vs 4.3%; p < 0.01), > or = 2 vasoactive drugs (61.9% vs 1.8%; p < 0.01), encephalopathy (37.5% vs 9.8%; p < 0.05), pneumonia (80% vs 8%; p < 0.01) and hemorrhage (29.4% vs 8.8%; p < 0.05). Graph ischemia, coagulopathy, reperfusion syndrome and use of blood derivatives during surgery were factors related with the development of complications and mortality. Multivariate analysis showed a relationship with mortality and low cardiac output, number of vasoactive drugs and total time of graft ischemia. Conclusions: Complications during the postoperative course of liver transplant are frequent but most of them have no effect on prognosis. The negative effect of severe complications should be limited by optimizing the hemodynamic support in these patients and minimizing ischemia of transplanted organs.
https://openpolicyfinder.jisc.ac.uk/id/publication/19939
Keywords: Hígado - Trasplante; Trasplante de órganos, tejidos, etc. - Factores de riesgo; Mortalidad; Cirugía - Complicaciones y secuelas; Liver Transplantation / adverse effects; Liver Transplantation / mortality; Intensive Care Units; Risk Factors